Study on neonatal morbidity in infants of diabetic mothers - Muthiah, Ravisankar; Pyarejan, Karamath S. (International Journal of Contemporary Pediatrics, 2020)
Background: Many infants of diabetic mothers (IDMs) born with specific characteristics like macrosomia, hypoglycemia, respiratory distress syndrome (RDS) and other morbidity risks. The present study was done with the aim to determine morbidity and mortality pattern amongst IDMs admitted into the neonatal intensive care units (NICU) of our tertiary care center. Methods: Descriptive study was done on 86 infants in the NICU of Government RSRM lying in Hospital and Institute of Social Pediatrics, Govt Stanley Hospital, Chennai Tamil Nadu during the period from August 2007 to October 2008. Data on mode of delivery, gestational age, birth weight, other associated morbidities and investigation results were noted. Results: Among the 85 mothers, 67 mothers had gestational diabetes mellitus and 18 had diabetes mellitus preceding pregnancy. Among the 86 IDMs, 15 infants were macrosomic, 11 infants were premature, 12 had mild to severe RDS, 11 infants had hypoglycemia, 3 had hypocalcemia, 2 had birth injuries, 3 infants were born as small for gestational age. Polycythemia observed in 3 IDMs, hyperbilirubinemia in 8 infants, external congenital malformations in two infants and congenital heart disease in three infants. Conclusions: IDMs developed many complications in the study. Macrosomia was the major among them. Perinatal morbidities can be reduced by screening of diabetic mothers from first trimester, maintaining good glycaemic control and adequate management of their infants.